2019
DOI: 10.1084/jem.20191002
|View full text |Cite
|
Sign up to set email alerts
|

The nature of human IL-6

Abstract: Countless functions have been attributed experimentally to IL-6. In this issue of JEM, Spencer et al. (https://doi.org/10.1084/jem.20190344) reveal essential, nonredundant functions of human IL-6. Patients with genetic deficiencies of the IL-6 receptor suffer from “hyper IgE syndrome.”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…Conversely, IL-6 (produced at comparable levels by the cells cultured in both supplements) is naturally connected with impaired inflammatory responses to localised tissue damage or with the impaired induction of acutephase proteins. In addition, it has previously been stated that "IL-6-producing cells" include bone marrow stromal cells, fibroblasts, and T cells [39], which supports our finding of the comparable levels of the formation of IL-6 by the MSCs cultured in both the iFBS-and PR-SRGF-supplemented media. The question is, therefore, whether the levels of particular pro-and anti-inflammatory molecules (defined by in vitro culturing) play a role or not (the level of IL-6 was one order of magnitude higher than the levels of IL-8, MCP-1, and RANTES) in the prediction of the balance of the immune response.…”
Section: Impact Of a Serum Alternative (Pr-srgf) On The Mscssupporting
confidence: 92%
“…Conversely, IL-6 (produced at comparable levels by the cells cultured in both supplements) is naturally connected with impaired inflammatory responses to localised tissue damage or with the impaired induction of acutephase proteins. In addition, it has previously been stated that "IL-6-producing cells" include bone marrow stromal cells, fibroblasts, and T cells [39], which supports our finding of the comparable levels of the formation of IL-6 by the MSCs cultured in both the iFBS-and PR-SRGF-supplemented media. The question is, therefore, whether the levels of particular pro-and anti-inflammatory molecules (defined by in vitro culturing) play a role or not (the level of IL-6 was one order of magnitude higher than the levels of IL-8, MCP-1, and RANTES) in the prediction of the balance of the immune response.…”
Section: Impact Of a Serum Alternative (Pr-srgf) On The Mscssupporting
confidence: 92%
“…No deficiencies of IL-27RA or ciliary neurotrophic factor receptor have been described, but most of the immunological and extrahematopoietic phenotypes of patients with AR partial or complete GP130 deficiency have been seen in patients lacking IL-6R, IL-11R, LIF-R, or OSM-R deficiency (Schwerd et al, 2017;Shahin et al, 2019;Spencer et al, 2019;Nieminen et al, 2011;Mikelonis et al, 2014;Arita et al, 2008). Collectively, these findings suggest that many, perhaps even most, of the immunological abnormalities seen in patients with STAT3 deficiency, whether biological (high IgE levels), clinical (atopy and recurrent staphylococcal infections), or both (low levels of inflammation), are due to poor cellular responses to IL-6 (Puel and Casanova, 2019), whereas most of the skeletal abnormalities are due to poor responses to IL-11 (craniosynostosis and deciduous tooth retention) or LIF (scoliosis, osteoporosis). The apparent lack of CMC in patients with AR deficiency of IL-6R, IL-10RA, IL-10RB, IL-11R, IL-21R, IL-23R, IFNAR1, IFNAR2, LIF-R, or OSM-R deficiency (Schwerd et al, 2017;Spencer et al, 2019;Nieminen et al, 2011;Mikelonis et al, 2014;Arita et al, 2008;Martínez-Barricarte et al, 2018;Hernandez et al, 2019;Glocker et al, 2011;Kotlarz et al, 2014;Duncan et al, 2015) also suggested that the pathogenesis of impaired IL-17 immunity and CMC in patients with mutations in STAT3 or ZNF341 may involve the disruption of multiple cytokine responsive pathways (Minegishi et al, 2007;Puel et al, 2011;Béziat et al, 2018;Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…On the contrary, the absence of IL-6 activated signaling pathway leads to bacterial infections, such as, staphylococcal disease, and abnormal responses of the immune system including the presence of high levels of immunoglobulins E and eczema. 2 Moreover, IL-6 levels were shown to increase with age. 23 This corroborates with our finding that IL-6 values increased by 0.05 pg/ml per year of age in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%